Reliance on Accounting Information, Budgetary Participation, and Task Uncertainty: Tests of a Three-Way Interaction - Brownell, Peter; Hirst, Mark (Journal of Accounting Research, 1986)
A series of studies reported in this Journal has addressed the question of whether evaluative styles of managers, which vary in terms of their reliance on accounting-based performance assessments, have systematically different behavioral consequences. These studies have produced conflicting results. In particular, Otley [1978] failed to confirm Hopwood's [1972] earlier findings that evaluative styles dominated by a heavy reliance on accounting performance measures, or a high budget-emphasis (BE), had adverse effects on job-related tension (JRT) and managerial performance. In two independent attempts to reconcile this conflict, Brownell [1982] found that a high (low) BE had positive effects on performance so long as budget participation is also high (low), and Hirst [1983] found that a high (low) BE is associated with low JRT in situations of low (high) task uncertainty. In this paper we report the results of a study which links the Brownell and Hirst attempts to reconcile the above conflict. More specifically, our objective was to assess the extent to which Brownell's finding also depends on the level of task uncertainty, the primary independent variable in the Hirst study. Arguments are presented which predict that